Calibrating Real‐World Evidence Studies Against Randomized Trials: Treatment Effectiveness of Infliximab in Crohn's Disease. Issue 1 (14th June 2021) - Kirchgesner, Julien; Desai, Rishi J.; Beaugerie, Laurent; Kim, Seoyoung C.; Schneeweiss, Sebastian
Abstract : Real‐world evidence (RWE) on the effectiveness of treatments in Crohn's disease (CD) derived from clinical practice data will help fill many evidence gaps left by randomized controlled trials (RCTs). Emulating RCTs with healthcare database studies may calibrate RWE studies in CD. We aimed to emulate the SONIC trial on the effectiveness of infliximab in patients with CD using US and French healthcare claims data. SONIC had shown improved remission with combination therapy (i.e., infliximab plus thiopurines) compared with infliximab monotherapy. Using claims data (2004–2019) from commercially insured patients in the United States (IBM MarketScan and Optum) and France (Système National des Données de Santé (National Healthcare Data System) (SNDS)), we conducted a cohort study of patients with CD who initiated combination therapy and compared them with patients who initiated infliximab alone. The primary outcome was a composite end point of treatment failure including hospitalization or surgery related to CD, treatment switch, or continuation of corticosteroids 26 weeks after infliximab initiation. Risk ratios (RRs) with 95% confidence intervals (CIs) were estimated in propensity score (PS)–matched cohorts. We identified 1, 437 PS‐matched pairs of combination therapy vs. infliximab monotherapy users. As in SONIC, the risk of treatment failure was decreased with combination therapy in the overall cohort (RR, 0.71; 95% CI, 0.62–0.82; RR, 0.78; 95% CI, 0.62–0.97 in SONIC). Findings were consistent across MarketScan, Optum, and SNDS databases: RR (95% CI), 0.83 (0.63–1.10), 0.66 (0.46–0.93), and 0.68 (0.57–0.82), as well as component end points. These robust findings highlight opportunities in RWE analysis for studying treatment effectiveness in patients with CD in clinical practice.